2018
DOI: 10.1172/jci.insight.98791
|View full text |Cite
|
Sign up to set email alerts
|

Peptide vaccine immunotherapy biomarkers and response patterns in pediatric gliomas

Abstract: Low-grade gliomas (LGGs) are the most common brain tumor affecting children. We recently reported an early phase clinical trial of a peptide-based vaccine, which elicited consistent antigen-specific T cell responses in pediatric LGG patients. Additionally, we observed radiologic responses of stable disease (SD), partial response (PR), and near-complete/complete response (CR) following therapy. To identify biomarkers of clinical response in peripheral blood, we performed RNA sequencing on PBMC samples collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Specifically, while DCs and CD8 + T cells increased over time, there was also a corresponding increase in immunosuppressive M-MDSCs and a decrease in B cells. The increase in DCs is of particular interest because it has been shown that DCs from the circulation are more effective at activating an antitumoral immune response than resident antigen presenting cells such as microglia (61)(62)(63). This phenomenon of immune recognition without an antitumoral immune response has also been observed in clinical trials of immunotherapies (63).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, while DCs and CD8 + T cells increased over time, there was also a corresponding increase in immunosuppressive M-MDSCs and a decrease in B cells. The increase in DCs is of particular interest because it has been shown that DCs from the circulation are more effective at activating an antitumoral immune response than resident antigen presenting cells such as microglia (61)(62)(63). This phenomenon of immune recognition without an antitumoral immune response has also been observed in clinical trials of immunotherapies (63).…”
Section: Discussionmentioning
confidence: 98%
“…The increase in DCs is of particular interest because it has been shown that DCs from the circulation are more effective at activating an antitumoral immune response than resident antigen presenting cells such as microglia (61)(62)(63). This phenomenon of immune recognition without an antitumoral immune response has also been observed in clinical trials of immunotherapies (63). The associations identified between GBM patients and their immunosuppression status with increasing MDSCs paves the way for future studies to combine anti-MDSC therapy with immune checkpoint therapies to enhance efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, while DCs and CD8 + T cells were increased over time, there was also a corresponding increase in immunosuppressive M-MDSCs and a decrease in B cells. The increase in DCs is of particular interest because it has been shown that DCs from the circulation are more effective at activating an anti-tumoral immune response than resident cells with MHC II such as microglia [57][58][59]. This phenomenon of immune recognition without an anti-tumoral immune response has also been observed in clinical trials of immunotherapies [59].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in DCs is of particular interest because it has been shown that DCs from the circulation are more effective at activating an anti-tumoral immune response than resident cells with MHC II such as microglia [57][58][59]. This phenomenon of immune recognition without an anti-tumoral immune response has also been observed in clinical trials of immunotherapies [59]. The associations identified between GBM patients and their status of immunosuppression with increasing MDSCs paves the way for future studies to combine anti-MDSC therapy with immune checkpoint therapies to enhance efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…118 The field is therefore moving along three non-mutually exclusive directions: (1) combining peptide-based vaccination with additional forms of (immuno)therapy, with the specific aim of reverting immunosuppression and enabling therapeutically relevant immune responses, 270-272 (2) targeting private antigenic epitopes that originate from mutations affecting only malignant cells (or sub-populations thereof), with PPV, 167,272-275 and (3) identifying specific patient populations that may obtain clinical benefit from the use of peptide-based vaccination. 174,254 Although the feasibility of PPV on a large scale remains unclear, we surmise combining some variants of peptide-based vaccination with potent immunostimulatory agents including immune checkpoint blockers and oncolytic viruses may be the key to unlock the true potential of this hitherto unrealized therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%